Hydrodynamic elements of aerosol flows for targeted drug delivery into the respiratory tract; Journal of Aerosol Science; Vol. 193 - Antonov D. V. Dmitry Vladimirovich; Kerimbekova S. A. Susanna Aleksandrovna; Nagatkina O. V. Olga Vladimirovna; Suvorova O. A. Olga Aleksandrovna (2026, 2026)
Title screen